Performance Reviewed from the Mutation, Leadership Style, Motivation and Discipline of Employees at the Class II Tuban Penitentiary - Renaldy Caesar Adytama Putra; Istiatin Istiatin; Sudarwati Sudarwati (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
This study aims to determine and explain the influence of transfers, leadership style, motivation, and discipline on the performance of employees at the Class II Tuban Penitentiary. The population of this study was 102 employees at the Class II Tuban Penitentiary, and a sample of 50 employees was selected using a total sampling technique. Data collection used a questionnaire. Data analysis used Multiple Linear Analysis. The results showed that transfers, leadership style, motivation, and discipline contributed 80.5% to performance, while the remaining 19.5% was explained by other variables not included in this study. The recommendations from this study are that employees at the Class II Tuban Penitentiary can improve their motivation and discipline, and that leaders can effectively manage the employee transfer system within their leadership, thereby further enhancing optimal performance at the Class II Tuban Penitentiary.